Solvent‐ and Ligand‐free Diboration of Alkynes and Alkenes Catalyzed by Platinum Nanoparticles on Titania. Issue 3 (6th February 2014) - Alonso, Francisco; Moglie, Yanina; Pastor‐Pérez, Laura; Sepúlveda‐Escribano, Antonio
Abstract Platinum nanoparticles supported on titania efficiently catalyzed the diboration of alkynes and alkenes under solvent‐ and ligand‐free conditions in air. The cis‐1, 2‐diborylalkenes and 1, 2‐diborylalkanes were obtained in moderate to excellent yields following, in most cases, a simple filtration workup protocol. The versatility of the cis‐1, 2‐diboronvinyl compounds was demonstrated in a series of organic transformations, including the Suzuki–Miyaura cross coupling and the boron–halogen exchange.